Nanocomposites of graphene/polymers: a review. Issue 83 (9th September 2015) - Chee, W. K.; Lim, H. N.; Huang, N. M.; Harrison, I.
<x xml:space="preserve">Abstract</x> Graphene-based nanofillers and their applications. Fabrication methods of graphene-based nanocomposites. Interaction and dispersion of graphene-based fillers in polymer matrices. Current trends and prospects of graphene-based nanocomposites.